Valutazione dell’esposizione a idrocarburi policiclici aromatici in addetti ad opere di asfaltatura autostradale mediante misura di 1-idrossipirene urinario / Asessment of exposure to polycyclic aromatic hydrocarbons in asphalt workers by measurement of urinary 1-hydroxypyrene - Campo, L.; Calisti, R.; Polledri, et al., E. (La Medicina del Lavoro, 2011)
SummaryIntroduction: Asphalt workers are potentially exposed to polycyclic aromatic hydrocarbons (PAHs). As some PAHs are classified as carcinogenic, the assessment of occupational exposure to these agents is of the utmost importance in preventing toxic effects. Objectives: To assess exposure to PAHs by urinary 1-hydroxypyrene (1-OHPyr). Methods: We studied 22 asphalt workers (14 smokers) and 5 control subjects (1 smoker). Multiple samples of urine (up to 4 per subject) were collected at the end of the shift for the measurement of 1-OHPyr by LC-MS/MS. Univariate and multivariate linear models for repeated measurements were used to evaluate the differences between groups and to identify the variables influencing of exposure. Results: The median urinary excretion of 1-OHPyr in asphalt workers was low, but higher than that of control subjects (184 vs.